VD_FINDINFO HC / 2020 / 708 vom 17. November 2020 - VD Tribunal cantonal (2020)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, TORT MORAL, JUSTE MOTIF, INTÉRÊT MORATOIRE | 321b CO, 328 CO, 337c al. 3 CO, 49 CO